An efficient and confluent approach for the synthesis of novel 3, 4-dihydro-2H-naphtho[2, 3-e][1, 3]oxazine-5, 10-dione derivatives by a three component reaction in ionic liquid1. Issue 58 (25th June 2015) - Khanna, Garima; Aggarwal, Komal; Khurana, Jitender M.
<x xml:space="preserve">Abstract</x> Novel 3, 4-dihydro-2H-naphtho[2, 3-e][1, 3]oxazine-5, 10-diones have been synthesized via one pot condensation of 2-hydroxy-1, 4-naphthoquinone, aromatic amine and formaldehyde in [bmim]BF4.